The effect of a video tutorial to improve patients’ keratoconus knowledge – a randomized controlled trial and meta-analysis of published reports - Sommer, Chiara; Bachmann, Lucas M.; Handzic, Armin; Iselin, Katja C.; Sanak, Frantisek; Pfaeffli, Oliver; Kaufmann, Claude; Thiel, Michael A.; Baenninger, Philipp B. (Frontiers in Ophthalmology, 2022)
Objective: To investigate whether a video tutorial, highlighting important aspects of keratoconus provided prior to a scheduled follow-up consultation, has a specific effect on patients’ knowledge after the consultation. Methods and Analysis: Single center, randomized controlled trial registered on ISRCTN registry (number ISCTN75317089, https://doi.org/10.1186/ISRCTN75317089). Consenting eligible keratoconus patients were randomly assigned to either receive a conventional face-to-face consultation (control group) or to an additional video tutorial (interventional group) on definition, risk factors and treatment options provided prior to the consultation. The main outcome measure was the difference of knowledge assessed by a questionnaire after the consultation. Of each participant, clinical characteristics, highest educational level and medical background were obtained. We also performed a meta-analysis of published reports assessing knowledge improvement by video-based patient education. Results: We assigned 22 patients to the interventional and 21 patients to the control group. Mean age was 29.0 years (SD 11.6), 8/43 (18.6%) were female and median disease duration was 2.5 years (interquartile range: 2-5years). Compared to the control group, knowledge was 12.0% (95%CI: 5.8%-18.2%; p<0.001) higher in the interventional group. Subjects with a university degree scored 6.8% (95%CI: 3.8%-13.3%; p=0.038) higher. There was no interaction between video information and university degree. Other parameters were not associated with patient knowledge. The meta-analysis of 566 subjects enrolled in 6 studies revealed a standardized mean difference in favor of video-based education of 0.47 (95% CI: 0.30-0.64; p<0.004) Conclusion: The results suggest that supplementary video information embedded in the clinical management of keratoconus, helps conveying relevant disease knowledge.